De novo assembly of a chromosome-level reference genome of the ornamental butterfly Sericinus montelus based on nanopore sequencing and Hi-C analysis - Li, Jingjing; Wang, Haiyan; Zhu, Jianqing; Yang, Qi; Luan, Yang; Shi, Leming; Molina-Mora, José Arturo; Zheng, Yuanting (Frontiers in Genetics, 2023)
Sericinus montelus (Lepidoptera, Papilionidae, Parnassiinae) is a high-value ornamental swallowtail butterfly species widely distributed in Northern and Central China, Japan, Korea, and Russia. The larval stage of this species feeds exclusively on Aristolochia plants. The Aristolochia species is well known for its high levels of aristolochic acids (AAs), which have been found to be carcinogenic for numerous animals. The swallowtail butterfly is among the few that can feed on these toxic host plants. However, the genetic adaptation of S. montelus to confer new abilities for AA tolerance has not yet been well explored, largely due to the limited genomic resources of this species. This study aimed to present a chromosome-level reference genome for S. montelus using the Oxford Nanopore long-read sequencing, Illumina short-read sequencing, and Hi-C technology. The final assembly was composed of 581.44 Mb with an expected genome size of 619.27 Mb. Further, 99.98% of the bases could be anchored onto 30 chromosomes. The N50 of contigs and scaffolds was 5.74 and 19.12 Mb, respectively. Approximately 48.86% of the assembled genome was suggested to be repeat elements, and 13,720 protein-coding genes were predicted in the current assembly. The phylogenetic analysis indicated that S. montelus diverged from the common ancestor of swallowtails about 58.57–80.46 million years ago. Compared with related species, S. montelus showed a significant expansion of P450 gene family members, and positive selections on eloa, heatr1, and aph1a resulted in the AA tolerance for S. montelus larva. The de novo assembly of a high-quality reference genome for S. montelus provided a fundamental genomic tool for future research on evolution, genome genetics, and toxicology of the swallowtail butterflies.